The representation of African traditional religion and culture in Nigeria popular films - Uwah, Innocent E. (Politikologija religije, 2011)
One of the ways by which religious rituals communicate in African society is by maintaining cohesion in the culture. They connect participants to richer meanings and larger forces of their community. Even in representational models, rituals create solidarity in the form of subjective experiences of sharing the same meaningful world which is attained by participants through the condensed nature of symbols used therein. Traditional religion is one ritual that despite the influence of westernization and scientific developments in Africa, still holds meaningful implications in people’s everyday life. Thus, from day break to evening, people have religious rituals with which they communicate with their God or gods, deities and ancestors. Also from weeks to seasons, months to years, there are festivals and rituals both in private and in public situations which the African still celebrate in connection with the ‘living dead’ or those in the ‘spirit world’. This paper by means of nuanced textual analysis of some Nigerian home based films: Things Fall Apart (1986), Igodo: The Land of the Living Dead (1999), Sango, (1998), Festival of Fire, (1999), Bless Me, (2005) traces religion to the root paradigm of African cultures as a channel to the construction of African identity
free
Keywords: Culture and religion; Film criticism; Films – Religious aspects; Nigeria.; Ritual – Study and teaching; Turner; Victor W (Witter); 1920-1983